Pertanggungjawaban Direksi Setelah Pemberian Acquit and Discharge - Johan, Suwinto; Ariawan, Ariawan (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 5 No 3 (2020), 2020)
This research paper objectives to discuss the acquit and discharge of the managing role by directors and supervising role by board of commissioners of the corporation. The research used a sample of the annual general meeting of shareholders of 32 public listed companies and 1 district court decision against the directors of a finance company on charges of falsifying company documents. This research uses judicial normative research method combined empirical data. The results show that the absence of acquit and discharge of directors and board of commissioners regulated in the limited company law, acquit and discharge are not entirely an agenda at the general meeting of shareholders and directors or board of commissioners can still be held for accountable, even though acquit and discharge have been given at the annual general meeting of shareholders.